Funktіonal aspect of munіtsipal-legal norms - Дутка, М. Т. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
Considered the question in the area of specific functional aspects norms of law in municipal law.Describes the theoretical-legal nature of the theory of «functions», «functions norm of the law» with the useof appropriate scientific analysis. Outlined content and formulate understanding «functions of norms ofmunicipal-law».